Retrospective analysis of poisoning cases in the pediatric intensive care unit (Annals of Medical Research, 2023)
Aim: According to the World Health Organization (WHO) data, poisonings are still a significant reason for mortality and morbidity in the childhood group. The rapid technological developments and the change in socio-cultural structures have caused an increase in chemical substances in homes, and the easy access of children to these chemicals has increased the possibility of poisoning. We aimed to make a retrospective analysis of patients with a diagnosis of poisoning hospitalized in the pediatric intensive care unit (PICU).Materials and Methods: The current clinical study is a retrospective, observational, single-center study and contains children adopted to the tertiary PICU of the 16-bed Batman Training and Research Hospital between March 2021 and March 2022 with a diagnosis of acute poisoning.Results: Forty patients were female (56.3%), and 31 patients were male (43.7%). All patients were admitted to the intensive care unit for advanced and supportive treatment. Supportive treatment was sufficient for 42 patients (59.2%). As advanced treatment; N-acetylcysteine infusion was given to 14 patients (19.7), oxygen to 3 patients (4.2%), inotropic support to 2 patients (2.8%), mechanical ventilatory support to 1 patient (1.4%), and antidote to 1 patient (1.4%). No mortality was observed, but some patients progressed morbidly and needed a mechanical ventilator and inotropic agent support.Conclusion: No mortality was observed, but some patients progressed morbidly and needed mechanical ventilatory support and inotropic agents. For this reason, the physician who first encounters the patient in the emergency department should evaluate each patient and the poison separately.
Keywords: Pediatrics; Intoxication; Poisoning; Intensive care